Ribosomal Tag Pyrosequencing of DNA and RNA Reveals "Rare" Taxa with High Protein Synthesis Potential in the Sediment of a Hypersaline Lake in Western Australia. Issue 5 (27th May 2016) - Weigold, Pascal; Ruecker, Alexander; Loesekann-Behrens, Tina; Kappler, Andreas; Behrens, Sebastian
ABSTRACT: Little is known about the potential activity of microbial communities in hypersaline sediment ecosystems. Ribosomal tag libraries of DNA and RNA extracted from the sediment of Lake Strawbridge (Western Australia) revealed bacterial and archaeal operational taxonomic units (OTUs) with high RNA/DNA ratios providing evidence for the presence of 'rare' but potentially "active" taxa. Among the 'rare' bacterial taxa Halomonas, Salinivibrio and Idiomarina showed the highest protein synthesis potential. Rare but 'active' archaeal OTUs were related to the KTK 4A cluster and the Marine-Benthic-Groups B and D. We present the first molecular analysis of the microbial diversity and protein synthesis potential of rare microbial taxa in a hypersaline sediment ecosystem.